Merih Erol, Greek Orthodox Music in Ottoman Istanbul: Nation and Community in the Era of Reform - Exertzoglou, Haris (Historein, 2018)
Merih Erol. Greek Orthodox Music in Ottoman Istanbul: Nation and Community in the Era of Reform. Bloomington: Indiana University Press, 2015. 264 pp.